REVIEWS. Issue 3 (6th December 2012) - Fears, Arthurina; Garnet, Dustin; Werner, James P.; Kantawala, Ami
WHY OUR HIGH SCHOOLS NEED THE ARTS, JESSICA HOFFMANN DAVIS (2012) New York: Teachers College Press/Reston, VA: National Art Education Association, 118 pp., ISBN 978-0-8077-5286-9, $23.95MATTER MATTERS: ART EDUCATION AND MATERIAL CULTURE STUDIES, PAUL E. BOLIN AND DOUG BLANDY (EDS) (2011) National Art Education Association, 157 pp., 62 mono illustrations, ISBN: 978-1-890160-51-7, $42.00. Reston, VA. Paperback.ART'S WAY OUT - EXIT PEDAGOGY AND THE CULTURAL CONDITION, JOHN BALDACCHINO (2012) Rotterdam; Boston, Sense Publishers, 204 pp., ISBN: 978-94-6091-792-6, Hardback: $99.00, Paperback: $39.00NATIONAL ART EDUCATION ASSOCIATION: ANNUAL CONVENTION, NEW YORK, 2012